Social and humanitarian policy of Ukraine in the conditions of war - Humeniuk T. (Науково-інформаційний вісник Івано-Франківського університету права імені Короля Данила Галицького)
Aim. The aim of this research is to highlight the influence of European integration on the optimization of the legal fundamentals of social policy in Ukraine. Methodology. The research is based on the comparative legal method used for comparison of EU social law with the social law of Ukraine. The method of dialectic enables to establish contradictions in the legal norms that regulate the social system of Ukraine and determine its social policy. The systemic and functional method was used to study the system of regulation of the sphere of social relations in Ukraine, systems of social policy measures as well as functional interrelationships between them. The method of generalization was used for the systematization and interpretation of the results obtained during the study.Results. The research showed that the main ways of improving social policy in Ukraine and legal regulation in the social sphere include: ratification of the European Social Charter and its implementation plan in Ukraine; creation of a coherent strategy in the field of provision of social services; the accession of Ukraine to the European Code of Social Security; partial reform of the legal regulation of labor and employment of the population; improvement of legal regulation and social policy in the field of social protection, labor and employment of internally displaced persons from temporarily occupied territories of Ukraine. Scientific novelty. During the research, it was established that on the way to the EU, Ukraine has faced the following problems with its social policy and law: problems with the Ukrainian legislation on social security; problems with regulating the labor market, employment and poverty reduction; problems with improvement of the legislation on labor protection; problems with stimulating entrepreneurship as the basis for ensuring social standards and employment of the population; problems with adaptation of socially vulnerable groups of the population.Practical significance. The results of the research can be used in international law.